The influence of lifestyle factors on constipation – should the pharmacist be aware of this? - Minkutė, Rima; Andrijauskaitė, Indrė; Briedis, Vitalis (ScienceRise: Pharmaceutical Science, 2019)
Aim of this study was to analyze the influence of lifestyle (nutrition and physical activity) on constipation and evaluate the respondents’ attitude to this disorder. Methods. Pharmacy visitors who agreed to answer questions were included in the study. Data from respondents based on age (18-45 years old; 46-65 years old; above 65 years old) and body mass index (“normal,” “overweight,” “obese”) was analyzed. Nutrition and physical activity were analyzed for the purpose of identifying risk factors for constipation. Descriptive and comparative statistics were used – the respondents’ responses are presented in frequencies and percentages, Chi-square test was executed to measure association with knowledge, responses and gender, age, BMI. Results. The study identified a 12.8 % constant constipation rate in the study group with no significant differences between genders, however more males had no constipation problem (50.5 % vs 39.9 %). The age and body mass index had association with constipation (p<0.05). The consumption of coffee and/or tea was not related to constipation in the study group, however, the respondents’ motionless lifestyle was related to constant and occasional constipation (75.0 % and 41.1 %, respectively) (p<0.05). Conclusions. The consumption of carbohydrates, inadequate intake of fluids and motionless lifestyle were identified as risk factors for constipation in this study. Lifestyle modification recommendations might be included in the pharmacists’ consultation